'A Just and Liberal Landlord': Manliness, Work, and the Landed Gentleman in the Brontës' Novels. (3rd July 2017) - Nyborg, Erin
Abstract: The Brontës' many striking depictions of landowners are rife with ambiguities, particularly as these characters are seldom presented at work in their traditional roles as landlord and magistrate. While the Victorian landed gentleman's status was partially predicated on not having to work for money, both the new Victorian professional ideal and traditional conceptions of paternalist care affected the ways this class was viewed by middle-class commentators at mid-century. In the Brontës' novels, traditional paternalist responsibilities are fused with aspects of the professional ideal in depictions of reformed landed gentlemen, but even this new, ideal figure is represented as unsatisfactory. In this article, I consider how landowners were written about in contemporary periodicals and how the Brontës engage with these expectations. The Irish tenant and landlord problem, which was covered extensively in the periodical press, shaped Emily Brontë's Wuthering Heights in a profound way, as the novel serves as an important, but until now overlooked, reworking of Maria Edgeworth's representations of landowning masculinity in Castle Rackrent (1800). The Brontës repeatedly depict landowners retreating into the domestic sphere, which I argue forms an implicit narrative challenge to this figure's social authority. This article opens up new ground for the examination of Victorian discourse on professionalization in relation to the Brontës' works and a consideration of the ways in which this discourse was applied to landowners both in the periodical press and the Victorian novel.